Origen, taxonomía, anatomía y morfología de la planta de arroz (Oryza sativa L.) - Degiovanni Beltramo, Víctor M.; Berrío Orozco, Luis Eduardo; Charry Mercado, Roger E. (International Center for Tropical Agriculture, 2010)
Origin, taxonomy, anatomy, and morphology of the rice plant (Oryza sativa L.) Information is presented on the origin, development, taxonomy, anatomy, and morphology of rice. Historic aspects of the origin of Oryza sativa are examined and discussed based on an extensive literature review. Although rice cultivation dates back to prehistoric times, there are discrepancies regarding the origin of rice and the relationship between the genus Oryza and other grasses. The taxonomy of the species is detailed, focusing on the Oryzae tribe and its two subtribes (Oryzinae and Zizaniinae), the Oryza genus and its different sections, and the different types of O. sativa (indica, japonica, and javanica or bulu). The anatomy of the roots, internodes, leaves, panicle, and seed of the rice plant is also described and illustrated. Regarding the morphology of this annual grass, the form and structure of its main organs, which are grouped into vegetative organs (root, culm, leaves) and reproductive organs (panicle, rachis, spikelet, flower, seed), are described and illustrated. Distinctive characteristics are its hollow cylindrical culms formed by nodes and internodes, its flat leaf blades joined to the leaf sheath, an inflorescence called a panicle, and its plant height, which ranges from 0.4 m (dwarf varieties) to 7.0 m (floating varieties). The process of rice seed germination is also explained in detail.